Cardiovascular Risk Factors in Children and Adolescents With Obesity: Sex-Related Differences and Effect of Puberty - Guzzetti, Chiara; Ibba, Anastasia; Casula, Letizia; Pilia, Sabrina; Casano, Simona; Loche, Sandro (Frontiers in Endocrinology, 2019)
Objectives: To evaluate the effect of gender and puberty on cardiovascular risk factors (CVRF) in obese children and adolescents. Methods: 1409 obese patients (age 9.7 (2.2-17.9) y; 646 Male) were studied. Subjects were stratified according to Tanner pubertal staging and age into prepubertal ≤ and >6 ys (G1 and G2), pubertal stage 2-3 (G3), and pubertal stage 4-5 (G4). Waist circumference (WC), systolic and diastolic blood pressure (SP, DP), fasting plasma glucose, insulin, post Oral Glucose Tolerance Test glucose and insulin, and lipids were evaluated. Insulin resistance was evaluated by HOMA index. Patients with no CVRF were considered metabolically healthy (MHO). Results: The percentage of MHO patients was 59.8% in G1 while was consistently around 30% in the other groups. WC was more frequently abnormal in G2 males. Pubertal progression was associated with a decrease in WC abnormalities. SP was more frequently abnormal in G4 males and pubertal progression was associated with higher prevalence of abnormal SP in males. Pubertal progression was associated with an increase in hypertension rate in both sexes. HOMA was more frequently abnormal in G2 and G3 females. HDL, LDL, and TG were more frequently abnormal in G2 females. Dyslipidemia rate was higher in G2 females. Pubertal progression was associated with higher prevalence of abnormal HDL in males. Conclusions: Sex and pubertal status influence the frequency of abnormalities of CVRF in obese children and adolescents. CVRF are already present in prepubertal age. Identifying patients with higher risk of metabolic complications is important to design targeted and effective prevention strategies.